Sweet sleep : nighttime and naptime strategies for the breastfeeding family - Wiessinger, Diane (Ballantine Books, 2014)
"Sweet Sleep is the first and most complete book on nights and naps for breastfeeding families. It's mother-wisdom, reassurance, and a how-to guide for making sane and safe decisions on how and where your family sleeps, backed by the latest research. It's 4 A.M. You've nursed your baby five times throughout the night. You're beyond exhausted. But where can you breastfeed safely when you might fall asleep? You've heard that your bed is dangerous for babies. Or is it? Is there a way to reduce the risk? Does life really have to be this hard? No, it doesn't. Sweet Sleep is within reach. This invaluable resource will help you sleep better tonight in under ten minutes with the Quick Start guide--and sleep safer every night with the Safe Sleep Seven sort out the facts and fictions of bedsharing and SIDS learn about normal sleep at every age and stage, from newborn to new parent direct your baby toward longer sleep when he's ready tailor your approach to your baby's temperament uncover the hidden costs of sleep training and "cry it out" techniques navigate naps at home and daycare handle criticism from family, friends, and physicians enjoy stories and tips from mothers like you make the soundest sleep decisions for your family and your life"--